Neurobiological determinants of antisocial behavior - Radochoński, Mieczysław; Perenc, Adam; Radochońska, Anna (European Journal of Clinical and Experimental Medicine, 2009)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Understanding the role which is played by a factors determining development of antisocial disorders, is an important issue, both for cognitive and socio-economic reasons. In the past years the researchers were concentrated mostly on influence of psychosocial determinants of personality disorders. Recently they are distinctively concerned with the neurobiological basis to antisocial and aggressive behavior. The developing field of neuroscience is beginning to provide important insights into the neural mechanisms that underlie the cognitive and affective processes involved in antisocial behavior. As it is widely known, common feature of the antisocial and rule-breaking behavior is the failure to follow moral guidelines. Authors of this paper give a review which summarizes key findings from brain imaging re-search on both antisocial behavior. The key areas which found to be functionally or structurally impaired in antisocial populations include dorsal and ventral regions of the prefrontal cortex (PFC), amygdala, hippocampus, angular gyrus, anterior cingulate and temporal cor-tex. Also regions most commonly activated in moral judgment process consist of the polar/medial and ventral PFC, amygdala, angular gyrus and posterior cingulate. It is hypothesized that the rule-breaking behavior common to antisocial, violent and psychopathic individuals is a result of impairments in some of the structures (dorsal and ventral PFC, amyg-dala and angular gyrus) determining moral cognition and emotion processes. Impairments to the emotional component that comprises the feeling of what is moral is viewed as the primary deficit in antisocials, although some disruption to the cognitive and emotional components of morality (particularly selfreferential thinking and emotion regulation) cannot be ruled out. While this neurobiological predisposition is likely only one of several biosocial processes involved in the etiology of antisocial behavior, it raises significant moral issues for the legal system and medical ethics.